Cost-utility analysis of olanzapine versus combination of haloperidol-diazepam in patients with acute phase schizophrenia: An Indonesian context - Hesty Utami Ramadaniati, Yusi Anggriani, Fredrick Dermawan Purba, Desweri Muhareni (Journal of Applied Pharmaceutical Science, 2022)
This study aimed to estimate the cost per quality-adjusted life-year (QALY) of olanzapine versus the combination of haloperidol-diazepam in acute phase schizophrenia. An observational study was conducted in a psychiatric hospital in Indonesia involving acute phase schizophrenic patients receiving either olanzapine or combination of haloperidol and diazepam. The outcome measures included Positive and Negative Syndrome Scale (PANSS) score, length of stay in acute room, utility score, and QALY. PANSS score and utility score were rated by psychiatrists and nurses, respectively, at the initiation of study medicines and after patient stabilization (postintervention). Calculated costs were direct medical costs with third-party payer perspective. QALY was determined by multiplying the utility score by the duration of the treatment effect to provide the number of QALY gained. A total of 193 patients (102 in olanzapine group/OG vs. 91 in haloperidol-diazepam group/HG). Postintervention, PANSS score significantly decreased by 16.09 in OG and 14.64 in HG. Patients in the two groups spent similar amount of time in acute room (i.e., 3–6 days). Both groups showed no significant difference in utility score and QALY post-treatment. Olanzapine incurred higher costs (US 20.89/QALY) than the comparator ($US 18.10/QALY). In conclusion, the combination of haloperidol-diazepam was a cost-effective option for treating acute phase schizophrenia.
Keywords: Cost utility, quality of life, haloperidol, olanzapine, schizophrenia